2007
DOI: 10.1097/01.anes.0000278876.20263.a7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Butorphanol on Morphine-induced Itch and Analgesia in Primates

Abstract: Butorphanol is effective in attenuating systemic or spinal morphine-induced itch without reducing morphine analgesia. This study provides functional evidence that both partial MOR and KOR agonist actions contribute to the effectiveness of butorphanol as an antipruritic in primates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 33 publications
4
39
0
1
Order By: Relevance
“…However, as previously demonstrated, intrathecal morphine simultaneously produces both scratching and antinociception in monkeys, but not in rodents (Ko and Naughton, 2000;Ko et al, 2003a;Lee et al, 2003). The present study of KOR agonists as antipruritics in primates further extends the therapeutic application of KOR agonists under the context of spinal opioid analgesia (Ko et al, 2003a;Lee et al, 2007; the present study). More importantly, a recent study demonstrated that there are two separate populations of spinothalamic tract neurons responding to histamine versus nonhistaminergic pruritogenic agent, cowhage, in monkeys (Davidson et al, 2007).…”
Section: Opioids As Antipruritics In Primates 197supporting
confidence: 76%
See 2 more Smart Citations
“…However, as previously demonstrated, intrathecal morphine simultaneously produces both scratching and antinociception in monkeys, but not in rodents (Ko and Naughton, 2000;Ko et al, 2003a;Lee et al, 2003). The present study of KOR agonists as antipruritics in primates further extends the therapeutic application of KOR agonists under the context of spinal opioid analgesia (Ko et al, 2003a;Lee et al, 2007; the present study). More importantly, a recent study demonstrated that there are two separate populations of spinothalamic tract neurons responding to histamine versus nonhistaminergic pruritogenic agent, cowhage, in monkeys (Davidson et al, 2007).…”
Section: Opioids As Antipruritics In Primates 197supporting
confidence: 76%
“…Nalfurafine (0.1-1 g/kg), bremazocine (0.1-1 g/kg), or GR 89696 (0.01-0.1 g/kg) was administered intramuscularly 45 min after 0.03 mg of intrathecal morphine. This dose of intrathecal morphine was selected based on previous studies showing that it produced maximal scratching responses and antinociception, and it could be used to detect whether the test compound could attenuate scratching without interfering intrathecal morphine-induced antinociception (Ko and Naughton, 2000;Lee et al, 2007). In a separate experiment, the tail-withdrawal latencies were measured at the same time points (i.e., measurement per half hour) in the same monkeys that were given effective antiscratching doses of KOR agonists 45 min after intrathecal morphine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, such unique effects of intrathecal morphine in humans [2,31] can be modeled in monkeys, but not in rodents, as a single dose of morphine produced both antinociception and itch/scratching responses simultaneously in monkeys [17,20,24]. For studying opioid analgesics in vivo, the scratching response can be used as a selective behavioral endpoint corresponding to activation of MOP [18,25]. Given that pruritus is a long standing side effect associated with the use of intrathecal morphine [7,8], lack of scratching responses by intrathecal UFP-112 in monkeys strongly suggests that UPF-112 has the therapeutic potential as a spinal analgesic.…”
Section: Discussionmentioning
confidence: 99%
“…30,39 On the other hand, increased scratching is also considered as a behavioral response to itch sensation in rodents receiving pruritogenic agents. 16,23,25 Whether scratching behavior is pain-related or itch-related depends on the context. Several factors such as administration routes and species differences may also contribute to different results or interpretations in the behavioral pharmacology of itch.…”
mentioning
confidence: 99%